Pulmonary Embolism: A Late Complication of Pectus Excavatum Repair - YILDIZELİ, BEDRETTİN (WILEY, 2014)
The Ravitch operation is frequently performed to correct pectus excavatum with few and minor complications. We present a case of pulmonary embolism with pulmonary endarterectomy in a patient undergoing Ravitch repair for pectus excavatum 2 years ago.
Keywords: Ravitch Procedure; Pectus Excavatum; Pulmonary Embolism